IMPLEMENTASI KIT DUTA INDONESIA DALAM PEMBELAJARAN TEMATIK SEKOLAH DASAR - Santoso, Minto (Konstruktivisme : Jurnal Pendidikan dan Pembelajaran, 2020)
The purpose of this research is to find out how the implementation of thematic learning by using duta indonesia media kits can lead to fun learning. With the classroom action research approach the results of the study showed that 92% of the steps in the game can be applied, and effective in achieving maximum competency, which is indicated by less than 10% of students who received poor ratings in attitude assessment and the achievement of an average grade of 84.6. In addition, 84% of students expect to be able to reuse the duta indonesia kit in their next learning. This shows that the implementation of the duta indonesia kit in thematic learning can be carried out effectively.